2006
DOI: 10.1080/03602530600959391
|View full text |Cite
|
Sign up to set email alerts
|

Novel Pathways Associated with Quinone-Induced Stress in Breast Cancer Cells

Abstract: Hormone-dependent breast cancers that overexpress the ligand-binding nuclear transcription factor, estrogen receptor (ER), represent the most common form of breast epithelial malignancy. Exposure of breast epithelial cells to a redox-cycling and arylating quinone induces mitogen-activated protein kinase phosphorylation of the cytoskeletal filament protein, cytokeratin-8, along with thiol arylation of H3 nuclear histones. Exogenous or endogenous quinones can also induce ligand-independent nuclear translocation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Promising results were also reported for cyclodextrin conjugates [79]. Such prodrugs include nitroarenes [94], quinones [95], amidoximes [96], platinum(IV) complexes [38] [97] [98], and Noxides exemplified here with tirapazamine (5.63) [99 -102]. One such target is the human intestinal peptide transporter (hPEPT1) [80], which showed good affinity and good transport capacity toward amino acid ester prodrugs of antiviral agents [81].…”
Section: Fig 525mentioning
confidence: 93%
“…Promising results were also reported for cyclodextrin conjugates [79]. Such prodrugs include nitroarenes [94], quinones [95], amidoximes [96], platinum(IV) complexes [38] [97] [98], and Noxides exemplified here with tirapazamine (5.63) [99 -102]. One such target is the human intestinal peptide transporter (hPEPT1) [80], which showed good affinity and good transport capacity toward amino acid ester prodrugs of antiviral agents [81].…”
Section: Fig 525mentioning
confidence: 93%
“…vitamin C has antioxidant activity when it reduces oxidizing substances such as H 2 O 2 , however, at high doses it can also reduce metal ions leading to the generation of free radicals through the fenton reaction) (Uetaki et al, 2015); some anticancer drugs (i.e. adriamycin and other anthracyclines, bleomycin, and cisplatin which bind to DNA and generate ROS) (Kovacic and Wakelin, 2001); or quinones (highly redox active molecules which can redox cycle with their semiquinone radicals, leading to formation of ROS) (Benz et al, 2006). The chemical reactivity of the many different reactive species may vary by up to 11 orders of magnitude when assayed against a given target [with comparable rate constants of 7 × 10 9 l × mol −1 × s −1 for hydroxyl radicals (HO˙) versus 2 × 10 −2 l × mol −1 × s −1 for H 2 O 2 ] (Sies et al, 2017).…”
Section: Oxidative Stress and The Intracellular Redox State In Melanomentioning
confidence: 99%
“…Since the electron transport chain is an abundant source of mitochondrial superoxide radicals [Castello et al, 2006;Poyton et al, 2009;Cardoso et al, 2012], and menaquinone is known to undergo redox-cycling and generate reactive oxygen species [ Benz et al, 2006;Klaus et al, 2010], we conducted studies that demonstrate that ectopic TERE1 and TBL2 expression can affect the cellular levels of oxidative stress as evidenced by oxidation of the CellROX fluorogenic probe. We also found that ectopic TERE1 can increase caspase 3/7 activity two-fold.…”
Section: Mitochondrial Transmembrane Potential Oxidative and Nitrosmentioning
confidence: 99%